Spatial index relating urban environment to health lifestyle and obesity risk in men and women from different age groups - Oliveira, David Michel; Marques, Mara Lucia; Santos, Daniel dos; Spexoto, Maria Claudia Bernardes; Togashi, Giovanna Benjamin; Massini, Danilo Alexandre [UNESP]; Filho, Dalton Müller Pessôa [UNESP] (Public Library of Science (PLoS), 2020)
The challenge in the search for relationships between urban space, physical mobility, and health status, is detecting indicators able to link the environment with healthy life habits. Therefore, the objective was to design an urban index for the identification of urban environment propensity for physical activity (PA) and to determine how it relates to lifestyle and anthropometric parametrization of obesity. Participants (N = 318–60.4% women and 39.6% men) were recruited from a mid-sized city with epidemiology and morbidity rates below the average for the mid-west region of Brazil. Body mass index (BMI) was measured and a questionnaire was applied to gather information about PA and life habits. The spatial urban health index (SUHI) was designed in a geographic information system using data from demographic, environmental and urban physical features. The relationship between BMI and PA was verified with multiple linear regression, controlled for SUHI levels. Regarding the BMI of the population, 69.5% were classified in the eutrophic or overweight ranges, with no effect of gender and age. The SUHI classified 63.7% of the urban area favorable to PA. The PA routine was adequate (≥3 sessions with ≥1 h each) for ~80% of the population, as well as healthy habits such as non smoking (~94%) and non alcohol abuse (~55%). The SUHI strengthens the relationships of BMI to weekly frequency (r = -0.68; t = -9.4; p<0.001) and session duration (r = -0.66; t = -2.8; p<0.001) for the whole group by improving the explanatory coefficient in ~25% (R2 Adj = 0.61 to R2 Adj = 0.85). The SUHI indicated that the urban environment is able to promote healthy life habits by diminishing the “obesogenic” features of the city when physical structures are planned to facilitate PA, whatever the gender and age group.